Application of Profit Level Indicators in Transfer Pricing - Poškaitė, Dalia; Novikovas, Martynas (Ekonomika, 2006)
In 2004, the transfer pricing rules (the Order of the Minister of Finance No. IK123) were issued in Lithuania, under which all the transactions between associated parties have to he concluded at the market price, i.e. the transfer prices should be in line with the arm’s length principle. In practice, the arm’s length price usually is determined applying profit level indicators. Therefore, this article aims to present the methodology for application of the profit level indicators in transfer pricing: the selection of transfer pricing method, calculation of profit level indicators and establishment of arm’s length range. According to the Lithuanian transfer pricing rules, when choosing the best transfer pricing method, the available methods should be considered in the following order: 1. Comparable uncontrolled price method. 2. Resale price or cost plus method. 3. Profit split or transactional net margin method. Applying all the aforementioned transfer pricing methods, except the comparable uncontrolled price method, the arm’s length price is determined using the following profit level indicators: gross profit margin, operating profit margin, mark up on costs of goods sold, mark up on operating costs, return on assets, Berry ratio. The choice of the profit level indicator is usually depend on the activity the transaction party is engaged in, the type of intercompany transaction, the distribution of functions, risks and assets between transaction parties, the availability of information, etc.